Bradyarrhythmias in acute myocardial infarction: should thrombolysis lower the decision threshold for temporary pacing?. Issue 789 (July 1991) - Lim, C. W.; Bennie, M. J.; Lim, R.
Abstract : Both acute myocardial infarction and reperfusion therapy with thrombolytic agents may be associated with bradyarrhythmias, and there may be a case for 'prophylactic' insertion of a temporary pacing wire in selected patients. We describe 4 patients in whom clinical decisions had to be made concerning the appropriateness and timing of temporary pacing, and discuss the implications for modern guidelines on the indications for pacing in such a setting.